Pengaruh Intellectual Capital dan Corporate Governance terhadap Corporate Sustainable Growth - Ivonne Agustina Boediono; Herlina Lusmeida (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to examine and obtain empirical evidence on the influence of Intellectual Capital and Corporate Governance on Sustainable Growth. Sustainability has become a public concern to find out the prospects for the company's sustainability in the future by considering various aspects. In this study, testing the influence of Intellectual Capital on the company's sustainable growth calculated using MVAIC and Corporate Governance measured using Independent Commissioners, Gender Diversity and Size of the Board of Directors. This study uses a sample of manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) in 2017-2020. Data analysis was performed using multiple linear regression with the STATA application program. The results of this study indicate that Intellectual Capital has no significant effect on the growth of the company's sustainability. Meanwhile, Corporate Governance as proxied using Independent Commissioners shows a significant influence. Another proxy for Corporate Governance, namely Gender Diversity and Size of the Board of Directors, is known to have no effect and has a negative effect on the company's sustainability growth.